2022
DOI: 10.3390/sym14040771
|View full text |Cite
|
Sign up to set email alerts
|

Hermite–Hadamard Type Inclusions for Interval-Valued Coordinated Preinvex Functions

Abstract: The connection between generalized convexity and symmetry has been studied by many authors in recent years. Due to this strong connection, generalized convexity and symmetry have arisen as a new topic in the subject of inequalities. In this paper, we introduce the concept of interval-valued preinvex functions on the coordinates in a rectangle from the plane and prove Hermite–Hadamard type inclusions for interval-valued preinvex functions on coordinates. Further, we establish Hermite–Hadamard type inclusions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Taking inspiration from this approach, Zhao et al [35,36] recently employed the conventional integral operator to establish inequality (1.2) within the framework of interval inclusion relations. The authors of [37] introduced pre-invex functions on the plane with interval values and derived multiple double inequalities. Wannalookkhee et al [38] utilized quantum integrals to derive a double inequality on the plane and for other applications.…”
Section: 𝒢(𝜅𝜃 + (1 − 𝜅)𝜆) ≤ 𝜅𝒢(𝜃) + (1 − 𝜅)𝒢(𝜆)mentioning
confidence: 99%
“…Taking inspiration from this approach, Zhao et al [35,36] recently employed the conventional integral operator to establish inequality (1.2) within the framework of interval inclusion relations. The authors of [37] introduced pre-invex functions on the plane with interval values and derived multiple double inequalities. Wannalookkhee et al [38] utilized quantum integrals to derive a double inequality on the plane and for other applications.…”
Section: 𝒢(𝜅𝜃 + (1 − 𝜅)𝜆) ≤ 𝜅𝒢(𝜃) + (1 − 𝜅)𝒢(𝜆)mentioning
confidence: 99%
“…Alomari and Darus [18] employed log-convex functions on coordinates to build Hermite-Hadamard inequality and its several new forms. Lai et al [19] defined I.V preinvex mappings on the coordinates and developed the Hermite-Hadamard inequality and its different forms by using interval partial-order relations. Wannalookkhee et al [20] employed quantum integrals and discovered the Hermite-Hadamard inequality on coordinates, with applications spanning numerous disciplines.…”
Section: Introductionmentioning
confidence: 99%
“…Nasir et al [29] developed some Ostrowskitype results using a fractional approach by using preinvex functions via second derivatives. In [30], the authors developed new variants of double inequalities based on preinvex functions on a real plane. As a result of using preinvex mappings in fractal space, Yu et al [31] found error bounds on parameterized integral inequalities.…”
Section: Introductionmentioning
confidence: 99%